APPLICATION OF THE NUMBERED HEAD TOGETHER LEARNING MODEL TO IMPROVE SCIENCE LEARNING OUTCOMES OF PRIMARY SCHOOL STUDENTS IN PADANGSIDIMPUAN CITY - Syahril Syahril; Isra Widya Ningsih (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2024)
The learning model is a way that can help teachers achieve the target of student learning completeness. Without implementing a learning model, teachers will experience optimal learning outcomes, impacting student learning outcomes. This research aims to improve students' social studies learning outcomes through the Numbered Head Together (NHT) learning model. This type of classroom action research uses the Kurt Lewin model, which consists of planning, action, observation, and reflection. The main subjects in this research were class IV students at SD Negeri 200220 Padangsidimpuan, totaling 26 students consisting of 14 boys and 12 girls. The data collection instruments used test items and observation sheets. Data analysis techniques use qualitative and quantitative descriptions. The research results show that using the NHT model can improve student learning outcomes. As evidenced by the pre-cycle learning results, ten students completed with an average of 65.96, a completion percentage of 38.5%, in the first cycle of meeting 1, 14 students completed with an average of 69.80, a completion percentage of 53.84%, cycle I meeting 2 obtained 15 students who ended with an average of 70.19, a completion percentage of 57.7%, cycle II meeting 1 accepted 19 students who completed with an average of 76.34, percentage of completeness 73.07% and cycle II meeting 2 obtained 22 students completed with an average of 81.15, a completion percentage of 84.6%.